MODERN FEATURES OF THE DENTAL SYSTEM IN BOYS AND GIRLS IN THE KEMEROVO REGION - Киселева, Елена Александровна; Сергеева, Маргарита Владимировна; Иванова, Ольга Павловна; Тё, Елена Александровна; Киселев, Денис Сергеевич; Запорожец, Никита Константинович; Киселева, Ксения Сергеевна; Тё, Игорь Анатольевич; Черненко, Сергей Владимирович; Гарафутдинов, Динар Минзагитович (Medicine in Kuzbass, 2024)
The study made it possible to clarify and detail the level and structure of occurrence of various forms of dental anomalies in groups stratified by gender, race, place of residence and orthodontic treatment in the anamnesis. This is a key age for the formation of adult dental health. Clinical and metric diagnostic tests were conducted in 1574 people aged 18 years, and 534 Kemerovo residents of the same age participated in the assessment of the quality of life. Depending on the clinical and anthropometric indicators of facial ratios, the clinical condition of joints, clinical and morphological indicators of dental anomalies, dental contact disorders, the ratio of dentition in the sagittal, vertical and transversal planes. There is a high prevalence of dental anomalies of 75.1 %. The overall incidence of dental anomalies was 75.1 %, whereas 30.7 % (483) of residents of the Kemerovo region had a history of orthodontic treatment by the age of 18, and those with a normognathic type of bite in 60% had already undergone orthodontic treatment. According to biometric studies of jaw models, with the change of generations, there are changes in the anthropometric characteristics of the size of teeth and dentition, which may be due to changes in environmental, household and genetic aspects.